Comparing skin surface temperature to clinical documentation of skin warmth in emergency department patients diagnosed with cellulitis - Edward Harwick; Rebecca J. Schwei; Robert Glinert; Ambar Haleem; Jamie Hess; Thomas Keenan; Joseph A. McBride; Robert Redwood; Michael S. Pulia (Journal of the American College of Emergency Physicians Open)
Abstract Objective To compare clinical documentation of skin warmth to patient report and quantitative skin surface temperatures of patients diagnosed with cellulitis in the emergency department (ED). Methods Adult patients (≥18 years) presenting to the ED with an acute complaint involving visible erythema of the lower extremity were prospectively enrolled. Those diagnosed with cellulitis were included in this analysis. Participant report of skin warmth was recorded and skin surface temperature values were obtained from the affected and corresponding unaffected area of skin using thermal cameras. Average temperature (Tavg) was extracted from each image and the difference in Tavg between the affected and unaffected limb was calculated (Tgradient). Clinical documentation of skin warmth was compared to patient report and measured skin warmth (Tgradient >0°C). Results Among 126 participants diagnosed with cellulitis, 110 (87%) exhibited objective warmth (Tgradient >0°C) and 58 (53%) of these cases had warmth documented in the physical examination. Of those with objective warmth, 86 (78%) self‐reported warmth and 7 (6%) had warmth documented in their history of present illness (HPI) (difference = 72%, 95% confidence interval [CI]: 62%–82%; P < 0.001). A significant difference was observed for Tavg affected when warmth was documented (32.1°C) versus not documented (31.0°C) in the physical examination (difference = 1.1°C, 95% CI: 0.29–1.94; P = 0.0083). No association was found between Tgradient and patient‐reported or HPI‐documented warmth. Conclusions The majority of ED‐diagnosed cellulitis exhibited objective warmth, yet significant discordance was observed between patient‐reported, clinician‐documented, and measured warmth. This raises concerns over inadequate documentation practices and/or the poor sensitivity of touch as a reliable means to assess skin surface temperature. Introduction of objective temperature measurement tools could reduce subjectivity in the assessment of warmth in patients with suspected cellulitis.